Fast accurate MR thermometry using phase referenced asymmetric spin‐echo EPI at high field. Issue 2 (25th February 2013) - Streicher, Markus N.; Schäfer, Andreas; Ivanov, Dimo; Müller, Dirk K.; Amadon, Alexis; Reimer, Enrico; Huber, Laurentius; Dhital, Bibek; Rivera, Debra; Kögler, Carsten; Trampel, Robert; Pampel, André; et al.
<x xml:space="preserve">Abstract</x> Purpose A novel highly accurate method for MR thermometry, effective at high field, is introduced and validated, which corrects for slow and fast field fluctuations by means of reference images. Methods An asymmetric spin‐echo echo planar imaging sequence was made frequency‐selective to water or a reference substance by controlling the slice‐select gradient polarity and the duration of the excitation and refocusing radiofrequency pulses. Images were acquired pairwise, and the temperature‐sensitive water images were corrected for field fluctuations using the reference images. In a phantom radiofrequency heating experiment, dissolved dimethyl sulfoxide was used as a reference substance. Temperature stability was tested in vivo on the human brain, referenced using subcutaneous scalp fat. Water and fat phase images were acquired only 50 ms apart. Bloch simulations validated the frequency selection accuracy. Results Asymmetric spin‐echo imaging using a simple frequency selection method provides highly accurate referenced MR thermometry in phantoms and in vivo at 7 T. Effects of field fluctuations caused by field drift, breathing, and heart beat were corrected. The technique is highly robust against B1 inhomogeneities. Conclusion Frequency selection using gradient‐reversal can enable fast accurate referenced in vivo MR thermometry, assisting thermal characterization of radiofrequency coils and possibly in vivo SAR monitoring. Magn Reson Med 71:524–533, 2014. © 2013 Wiley Periodicals, Inc.